Map of Alberta - Mundy, C. G. (Mundy Map Co., 1923)
This is a map of Alberta in 1923 showing surveyed Dominion lands, forest reserves, First Nations reserves, parks & game reserves, coal fields, roads, railways, trails, cities and towns. It includes homesteads information and notes on river navigation, currents, trade, vegetation, fishing, timber, natural resources, natural gas and drilling for oil. "Western Canada series No. 1" Relief shown by contours, hachures, and spot heights. Includes homesteads information and notes on river navigation, currents, trade, vegetation, fishing, timber, natural resources, natural gas and drilling for oil. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ . Scale 1:1,457,280, or 23 miles to 1 inch. Shows surveyed Dominion lands, forest reserves, First Nations reserves, parks & game reserves, irrigable areas, coal fields, roads, railways, trails, cities and towns.